Marketing communication of small sports via livestreams focused on floorball - Zemánek, Jakub; Křenková, Eva; Král, Petr, 1979-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This bachelor's thesis examines marketing communication strategies for small sports, focusing on floorball in the Czech Republic and Austria, with emphasis on livestreaming platforms to boost popularity and secure funding. Through qualitative analysis of 13 semi-structured interviews with floorball stakeholders, the study identifies key challenges like a lack of financial means, insufficient infrastructure, and low audience interest, alongside goals such as expanding the membership base, improving promotion, and attracting spectators and sponsors. Findings reveal Czech floorball's advanced use of integrated marketing channels like national TV (ČT Sport), livestreaming platform Český Florbal TV, and promotional events, contrasting Austria's niche marketing approach. The thesis recommends targeting specific market segments, especially children and their parents, via interactive and personal marketing media, and sponsors via social networks or livestreams, which provide viewership statistics that often persuade sponsors and secure their financial support.
Vedoucí práce: Eva Křenková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses